Molecular architecture of the inner ring scaffold of the human nuclear pore complex - Kosinski, Jan; Mosalaganti, Shyamal; Appen, Alexander von; Teimer, Roman; DiGuilio, Amanda L.; Wan, William; Bui, Khanh Huy; Hagen, Wim J. H.; Briggs, John A. G.; Glavy, Joseph S.; Hurt, Ed; Beck, Martin (Science. First release, 2016)
Blueprint for a macromolecular machine - Nuclear pore complexes (NPCs) consist of around 1000 protein subunits, are embedded in the membrane that surrounds the nucleus, and regulate transport between the nucleus and the cytoplasm. Although the overall shape of NPCs is known, the details of this macromolecular complex have been obscure. Now, Lin et al. have reconstituted the pore components, determined the interactions between them, and fitted them into a tomographic reconstruction. Kosinski et al. have provided an architectural map of the inner ring of the pore. - Science, this issue pp. 10.1126/science.aaf1015 and 363 - Nuclear pore complexes (NPCs) are 110-megadalton assemblies that mediate nucleocytoplasmic transport. NPCs are built from multiple copies of ~30 different nucleoporins, and understanding how these nucleoporins assemble into the NPC scaffold imposes a formidable challenge. Recently, it has been shown how the Y complex, a prominent NPC module, forms the outer rings of the nuclear pore. However, the organization of the inner ring has remained unknown until now. We used molecular modeling combined with cross-linking mass spectrometry and cryo-electron tomography to obtain a composite structure of the inner ring. This architectural map explains the vast majority of the electron density of the scaffold. We conclude that despite obvious differences in morphology and composition, the higher-order structure of the inner and outer rings is unexpectedly similar. - Reconstitution, spectroscopy, and crystallography allow the construction of a model of the human nuclear pore. - Reconstitution, spectroscopy, and crystallography allow the construction of a model of the human nuclear pore.